Invasion palatum oral squamous cell carcinoma to the maxillary sinus investigation: case report - Gustianto, Yudhy; Fauziyah, Erlina; Hanafi, Eva Yulianti; Cahyareni, Firlana; Epsilawati, Lusi (Ikatan Radiologi Kedokteran Gigi Indonesia, 2026)
Objectives: This case report aims to analyze the specific characteristics of Oral Squamous Cell Carcinoma (OSCC) and its rare invasion of the palate. Case Report: A 49-year-old male patient came to the Dental Radiology Installation of RSGM FKG UNPAD with a referral letter for a Cone Beam Computed Tomography (CBCT) examination. Based on the patient's anamnesis, he complained of swelling on the roof of the mouth that had lasted for 3 months, accompanied by pain, trismus, and persistent bad breath. Oral hygiene was poor; there was plaque, stains, and pale gums. The patient is an active smoker, smoking 1-2 packs per day; there is no history of similar diseases in the family. On extraoral examination, facial asymmetry was found due to swelling on the right cheek. On intraoral examination, gingival hyperplasia was found, accompanied by ulceration and reddish lesions on the roof of the mouth. The patient previously underwent a biopsy and excision of the roof of the mouth. Previous panoramic X-ray results showed lesions with unclear boundaries. On CBCT radiography, bone damage with irregular bone invasion and signs of malignancy indicate the characteristics of Squamous Cell Carcinoma (OSCC). 3D CBCT examination can be performed to accurately analyze and determine further diagnosis. Conclusion: 3D CBCT radiography can be used as a supporting examination to analyze specific characteristics in OSCC cases. The results of CBCT analysis can be a guideline in planning pre-operative follow-up to be carried out.